Síntese de biodiesel do óleo de algodão utilizando óxido de cálcio advindo da concha do sururu (Perna-perna) com adição do lítio em catálise heterogênea. - Carvalho, José Augusto Macedo (2022)
In this work, we sought to apply, evaluate and characterize calcium oxide, produced by thermal degradation of sururu (Perna perna) shells as a possible heterogeneous catalyst. The catalyst produced from the shell was tested in two stages. In the first step, the catalyst was composed of calcium oxide after calcination, in the second step, the catalyst would have the addition of lithium to calcium oxide, by the wet impregnation method at 1.5% by mass of CaO. For the characterization of the catalytic material, TGA, FTIR, XRD and SEM-EDS analyzes were performed. The analyzes showed that the thermal transformation of calcium carbonate into calcium oxide was satisfactory, so that the mass loss during this transformation was 46%, which changed the chemical composition and crystalline structure and there were no changes in morphology. of the catalyst. The reaction products were characterized by NMR analysis, acidity index, specific mass, calcium content and viscosity, and it was possible to observe the formation of methyl esters and the efficiency of lithium as an impregnated material. The reaction containing a molar ratio between alcohol and oil of 6:1 showed 90% conversion of the methyl esters, without the addition of lithium. After the addition of lithium, the conversion of methyl esters was 84%, showing the presence of high rates of leached calcium. Although the reaction with the best conversion rate was performed with a catalyst without the addition of lithium, it was possible to notice that there was a significant decrease in calcium leaching of approximately 30%. The application of catalyst reuse without lithium showed a conversion greater than 80% until the second reuse, with a conversion drop in the third and returning greater than 80% in the fourth reuse. While the addition of lithium only achieved a conversion above 80%, the others showed a conversion below 50%. Thus, the catalysts produced from sururu shells have high reactivity, good conversion of esters, and still good replicability in studies using lithium as an impregnating material during the production of biodiesel.